2012
DOI: 10.1590/s0080-62342012000600030
|View full text |Cite
|
Sign up to set email alerts
|

Cuidados com cateter central de inserção periférica no neonato: revisão integrativa da literatura

Abstract: The peripherally inserted central catheter is a common technology employed in the intravenous therapy of neonates. This integrative review was performed with the objective to investigate and analyze the evidence available in the literature regarding this technology. The databases searched included the Latin American and Caribbean Health Sciences Literature (LILACS) and the United States National Library of Medicine (PubMed). Results point at gaps in relation to their use in the neonatal population (n=1); vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
0
3
0
6
Order By: Relevance
“…Deve-se adotar medidas preventivas de infecção de corrente sanguínea (ICS) relacionada ao cateter 1,13 , tais como: barreira máxima na inserção, higienizar as mãos antes e após a manipulação do PICC; realizar a desinfecção das conexões e do hub com álcool à 70% antes da infusão de qualquer solução; substituir periodicamente o sistema infusional (equipo, polifix,) conforme rotina estabelecida pelo fabricante ou pela unidade; proteger o PICC e as conexões durante o banho e remover o PICC tão logo não seja mais necessário 13,15,16 .…”
Section: Revisão De Literaturaunclassified
“…Deve-se adotar medidas preventivas de infecção de corrente sanguínea (ICS) relacionada ao cateter 1,13 , tais como: barreira máxima na inserção, higienizar as mãos antes e após a manipulação do PICC; realizar a desinfecção das conexões e do hub com álcool à 70% antes da infusão de qualquer solução; substituir periodicamente o sistema infusional (equipo, polifix,) conforme rotina estabelecida pelo fabricante ou pela unidade; proteger o PICC e as conexões durante o banho e remover o PICC tão logo não seja mais necessário 13,15,16 .…”
Section: Revisão De Literaturaunclassified
“…28 In relation to care for maintaining the catheter they emphasized the use of heparin to prevent obstruction, aseptic dressing technique and the pressure applied to the catheter and prevent disruption. 19,21,26,29,34 The continuous infusion of low dose of heparin (0.5 IU/ kg/h) into the fluids is an effective measure to reduce the occlusion of the catheter, allowing the completion of therapy without observing adverse effects. 26,34 The healing practice is essential in maintaining the PICC because it covers and prevents local trauma and contamination, and respect the aseptic technique and the evidence as to the material used and the frequency of change.…”
Section: Insertion and Maintenance Practices Categorymentioning
confidence: 99%
“…26,34 The healing practice is essential in maintaining the PICC because it covers and prevents local trauma and contamination, and respect the aseptic technique and the evidence as to the material used and the frequency of change. 21 In reporting experience with 491 catheters that evaluates technique of dressing with a protective base layer they concluded that catheter complication rates were low, and that dressing changes catheters wereminimized. 37 As for the pressure applied to the catheter and the risk of rupture, only one study addressed the issue.…”
Section: Insertion and Maintenance Practices Categorymentioning
confidence: 99%
“… 12 , 13 The lack of scientific evidence and standardization through protocols leads to the use of several heparin concentrations, which can often be abusive as well as be as underdoses, which can result in unknown side effects or failure in catheter clearance. 14 …”
Section: Introductionmentioning
confidence: 99%
“… 12 , 13 A falta de evidência científica e a não padronização por meio de protocolos levam ao uso de concentrações diversas, muitas vezes abusivas, e outras com subdosagens, que podem resultar em efeitos colaterais desconhecidos ou o insucesso na desobstrução. 14 …”
Section: Introductionunclassified